Biokeramik Hidroksiapatit (HAp) Berbahan Dasar Cangkang Tiram Anodonta nuttaliana dari Danau Poso - Agung Rimayanto Gintu; Elizabeth Betty Elok Kristiani; Yohanes Martono (Eksergi, 2020)
Bioceramic Hydroxyapatite (HAp) was a derivated chemical synthetic compound from calcium phosphate commonly used to care the damage of hard tissues. Bioceramic Hydroxyapatite can synthetized from the compounds which rich with calcium contains. In this study threated the synthesis and physicochemical characterization to the HAp made from Anodonta nuttaliana clam shells obtained from Poso lake. From the characterization of the sample A. nuttaliana shells obtained the water contains 0,50±0,00%; ash contains 0,9827±0,0022g/g; potasium 0,00135±0,0002g/g; calcium 0,0165±0,0034g/g; phosphate 0,1920±0,0424g/g and the ratio of Ca/P 1,9389±0,3039%. The synthesis of HAp by base precipitation method showed the yield of synthesis 95,4320±0,7085% with the characteristic of the HAp showed that the potassium contains 0,0005±0,00004g/g; calcium 0,95476±0,0012g/g; phosphate 0,528±0,0075; ratio of Ca/P 1,0307±0,0932%; porosity 73,9598±1,1320%; swelling ability 9,6067±2,5365%; and biodegradability 8,8206±0,2176%. From the overall results concluded that the A. nuttaliana clam shells was very potential to became a source of Bioceramic Hydroxyapatite (HAp).